Site-Specific Phosphorylation of Histone H1.4 Is Associated with Transcription Activation - Saha, Ankita (Int J Mol Sci, 2020)
Core histone variants, such as H2A.X and H3.3, serve specialized roles in chromatin processes that depend on the genomic distributions and amino acid sequence differences of the variant proteins. Modifications of these variants alter interactions with other chromatin components and thus the protein’s functions. These inferences add to the growing arsenal of evidence against the older generic view of those linker histones as redundant repressors. Furthermore, certain modifications of specific H1 variants can confer distinct roles. On the one hand, it has been reported that the phosphorylation of H1 results in its release from chromatin and the subsequent transcription of HIV-1 genes. On the other hand, recent evidence indicates that phosphorylated H1 may in fact be associated with active promoters. This conflict suggests that different H1 isoforms and modified versions of these variants are not redundant when together but may play distinct functional roles. Here, we provide the first genome-wide evidence that when phosphorylated, the H1.4 variant remains associated with active promoters and may even play a role in transcription activation. Using novel, highly specific antibodies, we generated the first genome-wide view of the H1.4 isoform phosphorylated at serine 187 (pS187-H1.4) in estradiol-inducible MCF7 cells. We observe that pS187-H1.4 is enriched primarily at the transcription start sites (TSSs) of genes activated by estradiol treatment and depleted from those that are repressed. We also show that pS187-H1.4 associates with ‘early estrogen response’ genes and stably interacts with RNAPII. Based on the observations presented here, we propose that phosphorylation at S187 by CDK9 represents an early event required for gene activation. This event may also be involved in the release of promoter-proximal polymerases to begin elongation by interacting directly with the polymerase or other parts of the transcription machinery. Although we focused on estrogen-responsive genes, taking into account previous evidence of H1.4′s enrichment of promoters of pluripotency genes, and its involvement with rDNA activation, we propose that H1.4 phosphorylation for gene activation may be a more global observation.